Lexical patterns in customary sayings - Jaafar, Mohammad Fadzeli (Universitas Pendidikan Indonesia, 2018)
Customary sayings are the traditional words delivered in the form of poetry and practiced in various social activities in Negeri Sembilan in marriage, family, criminal law and administration. Sudeen (1995) recorded that studies on customary sayings have been conducted from the early 20th century in the history of custom, marriage system, political system and the dispensation of inheritance.This study examines the content words and function words in customary sayings that have been categorized based on the semantic domain concept by Gliozzo (2006).Â Based on the content words and function words, this study has identified the customary words in the corpus data. The results show that more function words were used in the customary sayings.Â However, content words dominated the list of customary sayings, such as Datuk and custom. The function words 'nan' and 'dek' were found in all domains of the study namely, political, social and economic domains. These findings indicate that function words are not only grammatically functional, but also used to give an aesthetic impact through the articulation style of the local dialect.Â On the other hand, the analysis of the content words shows that the use of customary words is influenced by the environment and culture of Adat Perpatih.